Physical-Exercise-Induced Antioxidant Effects on the Brain and Skeletal Muscle - Jennyffer Souza; Rodrigo Augusto da Silva; Débora da Luz Scheffer; Rafael Penteado; Alexandre Solano; Leonardo Barros; Henning Budde; Andrés Trostchansky; Alexandra Latini (Antioxidants, 2022)
Erythroid-related nuclear factor 2 (NRF2) and the antioxidant-responsive-elements (ARE) signaling pathway are the master regulators of cell antioxidant defenses, playing a key role in maintaining cellular homeostasis, a scenario in which proper mitochondrial function is essential. Increasing evidence indicates that the regular practice of physical exercise increases cellular antioxidant defenses by activating NRF2 signaling. This manuscript reviewed classic and ongoing research on the beneficial effects of exercise on the antioxidant system in both the brain and skeletal muscle.